2011
DOI: 10.5352/jls.2011.21.3.424
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Physical Activity Program on Body Composition, Depression and Risk Factors of Dementia in the Elderly Women

Abstract: The purpose of this study was to examine the effects of a physical activity program on body composition, depression and risk factors of dementia in elderly women. Subjects were 40 women aged 65~75 years, classified into two groups (experiment group 20, control group 20). The factors measured in this study were body composition (weight, percent body fat, body mass index, body fluid), depression (BDI score) and risk factors of dementia (K-MMSE, LDL-C, HDL-C, insulin, β-amyloid, DHEAs) at 12 and 24 weeks before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Prior studies on Aβ and exercise intensity in elderly females reported a significant decrease in Aβ after participants performed Taekwondo Poomsae at 50-75% HRR for 60 min per session three times a week for 12 weeks [35], a decrease in the Aβ index after participants performed a combination of physical stimulation and walking exercises at 60-70% of maximum heart rate for 45-60 min per session for 24 weeks [36], and a decrease in Aβ after participants performed combined aerobic and anaerobic exercises at 50-70% intensity of target heart rate for 60 min per session three times a week for 12 weeks [22].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on Aβ and exercise intensity in elderly females reported a significant decrease in Aβ after participants performed Taekwondo Poomsae at 50-75% HRR for 60 min per session three times a week for 12 weeks [35], a decrease in the Aβ index after participants performed a combination of physical stimulation and walking exercises at 60-70% of maximum heart rate for 45-60 min per session for 24 weeks [36], and a decrease in Aβ after participants performed combined aerobic and anaerobic exercises at 50-70% intensity of target heart rate for 60 min per session three times a week for 12 weeks [22].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies on Aβ and exercise intensity in elderly females reported a significant decrease in Aβ after participants performed Taekwondo Poomsae at 50-75% HRR for 60 minutes per session three times a week for 12 weeks [34], a decrease in the Aβ index after participants performed a combination of physical stimulation and walking exercises at 60-70% of maximum heart rate for 45-60 minutes per session for 24 weeks [35], and a decrease in Aβ after participants performed combined aerobic and anaerobic exercises at 50-70% intensity of target heart rate for 60 minutes per session three times a week for 12 weeks [21].…”
Section: Discussionmentioning
confidence: 99%
“…One of the social and environmental approaches to prevention and management of dementia is to apply exercise programs as much as possible. Recently, activity programs have received much attention; these programs aim to bring about behavioral changes and improvements in quality of life by increasing physical and mental functions through regular and systematic physical movements 2 ) . Regular exercise is extremely important for patients with dementia 3 ) , because it can activate brain metabolism, increase secretion of cerebral blood flow and neuro-transmitters 4 ) , and prevent damage in the internal blood vessel walls by increasing elasticity of the blood vessel walls 5 ) .…”
Section: Introductionmentioning
confidence: 99%